Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bengkel Maju Mandiri - Ayub, Putu Denny Prathama; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
Workshop is one of the businesses that are in the service industry, one of which is the Independent Forward Workshop. Service delivery is expected to provide maximum satisfaction to the consumer on Advanced Workshop Maju Mandiri. The aim of the studies to determined whether the dimensions of servqual affect the consumer statisfaction in the Independent Forward Workshop. The population in this study are all consumers at Maju Mandiri Workshop aged 17 years and over. The number of sample as taken by 126 respondents with a purposive samplings method. Data was collect by questionnaires, interviews. Based on regression analysis showed that the overall service quality positive effect on customer satisfaction in Maju Mandiri Workshop. These results indicate that the better quality of service will increase customer satisfaction. Keywords: Service quality, tangible, reliability, responsiveness, assurance,  empathy, and consumer satisfaction.